1993
DOI: 10.1038/366476a0
|View full text |Cite
|
Sign up to set email alerts
|

Functional ecdysone receptor is the product of EcR and Ultraspiracle genes

Abstract: Although the biological activity of the insect moulting hormone ecdysone, is manifested through a hormonally regulated transcriptional cascade associated with chromosomal puffing, a direct association of the receptor with the puff has yet to be established. The cloned ecdysone receptor (EcR) is by itself incapable of high-affinity DNA binding or transcriptional activation. Rather, these activities are dependent on heterodimer formation with Ultraspiracle (USP) the insect homologue of vertebrate retinoid X rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
552
0
12

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 892 publications
(580 citation statements)
references
References 20 publications
16
552
0
12
Order By: Relevance
“…This has been especially true for the critical third (final) larval instar when the insect must be reprogrammed so that it can undergo metamorphosis to the pupa and then the adult in response to a large surge in 20E, a phenomenon studied mainly in the Lepidoptera (Bollenbacher et al, 1975;Riddiford, 1976Riddiford, , 1995. The requisite involvement of ecdysteroid signaling in these complex processes is central to present theories of arthropod development (Ashburner et al, 1974;Yao et al, 1993;Buszczak and Segraves, 1998;Bialeccki et al, 2002;Lafont et al, 2005;Henrich, 2005). However, the RIA, particularly when applied directly to whole body extracts, yields only a rough estimate of the molting hormone titer, as each ecdysteroid component present gives a variable response (cross-reactivity) in the assay depending on affinity characteristics of the antibody used.…”
Section: Discussionmentioning
confidence: 99%
“…This has been especially true for the critical third (final) larval instar when the insect must be reprogrammed so that it can undergo metamorphosis to the pupa and then the adult in response to a large surge in 20E, a phenomenon studied mainly in the Lepidoptera (Bollenbacher et al, 1975;Riddiford, 1976Riddiford, , 1995. The requisite involvement of ecdysteroid signaling in these complex processes is central to present theories of arthropod development (Ashburner et al, 1974;Yao et al, 1993;Buszczak and Segraves, 1998;Bialeccki et al, 2002;Lafont et al, 2005;Henrich, 2005). However, the RIA, particularly when applied directly to whole body extracts, yields only a rough estimate of the molting hormone titer, as each ecdysteroid component present gives a variable response (cross-reactivity) in the assay depending on affinity characteristics of the antibody used.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of the ligand 1,25-dihydroxyvitamin D 3 enhanced the affinity of the vitamin D 3 receptor for RXR by 7-fold as a result of an increase in the association rate constant, and we hypothesize that the T 3 -mediated enhancement of the TR-RXR interaction might involve a similar mechanism. Another example in which ligand promotes dimerization is provided by the ecdysone receptor-ultraspiracle interaction, where muristerone has been shown to promote formation of ecdysone receptor-ultraspiracle complexes as well as formation of ecdysone receptor-ultraspiracle or ecdysone receptor-RXR heterodimers on DNA (48). Last, a genomic footprinting study has shown that occupancy of the retinoid response element in the RAR␤2 gene occurs only after treatment of cells with retinoic acid (49).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Zeste crosslinks in vivo to short regions of the Ubx promoter at at least 100-fold higher levels than it does to other genes (Walter et al, 1994;Laney and Biggin, 1997). Studies of proteins bound to polytene chromosomes also suggest that some transcription factors bind selectively to only a small number of genes (Urness and Thummel, 1990;Yao et al, 1993). We suggest that metazoan transcription factors will show a spectrum of DNA binding, from factors that bind very selectively to those that bind as broadly as Bicoid, Paired, Eve and Ftz.…”
Section: Transcription Factor Dna Binding In Vivomentioning
confidence: 98%